Material Objects as Promoters of a Resistant Subjectivity: The Creation of an Alternative Space in Chimamanda Ngozi Adichie's "Imitation" - Fuentes Antrás, Francisco (My University, 2021)
This article explores how Nkem, the female character in Chimamanda Ngozi Adichie's short story "Imitation" (2009), builds a resistance space from where she exalts her subjectivity and rebels against an oppressive marriage that voids her. Her physical and mental paralysis is mainly triggered by an absent and distant husband called Obiora, who forces his wife into a materialization process that translates into Nkem being gradually infected by the fakeness and voiceless condition of the art pieces that he brings home from Nigeria. Consequently, she is commoditized and turned into one more imitational art piece in Obiora¿s collection, stressing her immobility and dependence on her husband. However, the originality and uniqueness of the African Ife bronze head that Obiora brings with him at the end of the story trigger Nkem¿s reflection, leading her to also recognize her own value. Through the projection of her subjectivity on the original African art piece, Nkem takes advantage of her in-betweness as a Nigerian in the United States and her house¿s interstitial status to create a ¿third space¿ where she can redefine herself outside the patriarchal ideology that Obiora epitomizes, as well as retrieve the African identity she had lost during the reterritorialization process undergone in her white American neighborhood. The redefinition of her relationship with the surrounding African items and the consequent appropriation of the space that this implies empowers her, since ¿territoriality is a primary geographical expression of social power¿ (Sack 5) and our identities and self-definitions are inherently territorial (Agnew 179). Keywords resistance space; Adichie; third space; identity; materialization process